ACTIO FAMILIAE ERCISCUNDAE IN THE LAW CODE OF GORTYN AND IN THE CODE OF XII TABLES - Ristić, Milica (Glasnik Advokatske komore Vojvodine, 2023)
The author examines the relationship between the Greek and Roman legal traditions through the analysis of the actio familiae erciscundae or lawsuit for the division of family property, which is found both in the Law Code of Gortyn and in the Code of 12 Tables. Several scientific research methods were used in the paper. The comparative legal method is the most represented, with which the author will try to answer the question whether the actio familiae erciscundae can be labeled as a kind of legal transplant, and whether it is possible to derive from this relationship some more general conclusions about the degree of legal transplantation between the two great ancient systems. In order to provide the answer to that question, the historical method was also used in the paper, in order to better understand the socio-political context of the given time, as well as the linguistic method for the purpose of correctly interpreting the sense and meaning of the actio familiae erciscundae lawsuit. Although at first glance the existence of this lawsuit in two great ancient codes indicates certain similarities, a deeper analysis of the character of family union and property in Roman and Greek society reveals some essential differences presented in the paper, from which the author concludes that the degree of Greek influence on Roman law is somewhat overrated and overemphasized.
Keywords: actio familiae erciscundae, lawsuit for division of family property, Law Code of Gortyn, Code 12 tables, consortium.